2022
DOI: 10.3390/en15051737
|View full text |Cite
|
Sign up to set email alerts
|

City-Level Transition to Low-Carbon Economy

Abstract: In recent years climate change has emerged as a global issue directly related to quality of life. In this context, one of the key goals in the next few decades will be to transition the global economy to a sustainable system. The nature of the energy planning process dictates the application of complex models. There is no universal solution to the energy planning problem. Each territory requires a bespoke strategy aimed at utilising its specific potential. The research presented in this paper explores reaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…The research was conducted using both quantitative and qualitative methods, including analysis of legislation and interviews with representatives of car manufacturers. Xian et al (2022) Višković et al (2022) investigate the transition to a low-carbon economy through corporate energy management based on a survey of 184 large European companies to find out which corporate energy management practices are applied in the context of the transition to a low-carbon economy and what obstacles stand in the way of the transition. In addition, it was found that most companies are already taking concrete steps to reduce their carbon footprint, including using renewable energy sources, increasing energy efficiency, and improving energy management processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research was conducted using both quantitative and qualitative methods, including analysis of legislation and interviews with representatives of car manufacturers. Xian et al (2022) Višković et al (2022) investigate the transition to a low-carbon economy through corporate energy management based on a survey of 184 large European companies to find out which corporate energy management practices are applied in the context of the transition to a low-carbon economy and what obstacles stand in the way of the transition. In addition, it was found that most companies are already taking concrete steps to reduce their carbon footprint, including using renewable energy sources, increasing energy efficiency, and improving energy management processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that most companies are already taking concrete steps to reduce their carbon footprint, including using renewable energy sources, increasing energy efficiency, and improving energy management processes. However, Višković et al (2022) also point to some obstacles such as a lack of resources, limited availability of clean technologies, high investment costs in new technologies, and weak political leadership.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some clean energy technologies have been developed relatively maturely, such as wind and solar power generation [8]. Meanwhile, responsiveness, digitization, artificial intelligence, carbon trading, smart grids, and electric vehicles are contributing to lowcarbon city [9]. Some studies have analyzed the construction methods of city's energy system, including multi-objective optimization [10] [11], sector coupling [12], and scenario-based method [13].…”
Section: Introductionmentioning
confidence: 99%
“…Each region needs a tailored strategy that can optimally utilize its energy potential [9]. This paper describes a construction model of zero-carbon energy system towards carbon-neutral cities based on local produced renewable energy suitable for cities and towns.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, there has been an increasing quest for transition into a low carbon economy due to the adverse effect of the utilization of energy derived from fossil fuels on the environment [1]. The utilization of fossil-fuel-derived energy for various human activities often results in the emission of environmentally unfriendly gaseous emissions, with climate change being one of the most undesirable effects [2].…”
Section: Introductionmentioning
confidence: 99%